2020
DOI: 10.32737/2221-8688-2020-1-40-48
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHESIS AND CRYSTAL STRUCTURE OFA NEW 9P–TYPE LAYERED van der WAALSCOMPOUND SnBi4Te4

Abstract: Considering structural features of the already known tetradymite-like layered chalcogenide phases, we have attempt to synthesize a new mix-layered compound, SnBi 4 Te 4 . The newly synthesized alloy examined by means of differential thermal analysis, powder X-ray diffraction and scanning electron microscope techniques.The melting nature of the discovered phase is found to be incongruently at 831 K. The crystal structure of the SnBi 4 Te 4 was elucidated from powder pattern by Rietveld method. The determined cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…For MnSb4Te7, all diffraction patterns are indexed in the trigonal structure with lattice parameters a = 4.2413 Å and c = 23.761 Å. We note that determined unit cell parameters of MnSb2Te4 are in good agreement with already reported ones elsewhere in [27,28]. However, the narrow homogeneity field of the MnSb2Te4 compound may cause some deviation from the values of the a and c parameters which suggests that other results can also be acceptable.…”
Section: Resultssupporting
confidence: 81%
“…For MnSb4Te7, all diffraction patterns are indexed in the trigonal structure with lattice parameters a = 4.2413 Å and c = 23.761 Å. We note that determined unit cell parameters of MnSb2Te4 are in good agreement with already reported ones elsewhere in [27,28]. However, the narrow homogeneity field of the MnSb2Te4 compound may cause some deviation from the values of the a and c parameters which suggests that other results can also be acceptable.…”
Section: Resultssupporting
confidence: 81%
“…As the information on topological insulators increased [8,9], layered bismuth and antimony chalcogenides were also proven to host topological surface states [10][11][12]. Ongoing research in this field revealed that tetradymitelike ternary compounds formed in A IV -B V -Te systems (A IV -Ge, Sn, Pb; B V -Sb, Bi) systems including A IV B V 2 Te 4 , A IV B V 4 Te 7 , A IV B V 6 Te 10 are also three-dimensional topological insulators [13][14][15][16][17][18][19][20][21]. The creation of new multicomponent functional materials is possible based on the phase equilibria data of the corresponding systems.…”
Section: Introductionmentioning
confidence: 99%
“…Data analysis indicates that in A IV -B V -Te systems, besides above mentioned homologous series, there can also exist phases relevant to mBi2 -𝐴 𝐼𝑉 𝐵 2 𝑉 Te4 homologous series. The first two members of this series have been reported in recent years: SnBi4Te4 [34] and GeSb4Te4 [35]. Identification of these compounds increases the probability of such phases in a similar Ge -Bi -Te system.…”
Section: Introductionmentioning
confidence: 99%